Pluralism Values in The History of Islamic Culture (Analysis Study on Teaching Material of Class XII Madrasah Aliyah) - Yu suf (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This study aims to find out how and whether or not there are pluralism values in the history of Islamic culture in the analysis of teaching materials of Class XII madrasah aliyah/Senior High School, therefore this research used qualitative or library research methods because this study examines the sources that comprise the literatures related to the title. The type of research is library (library research), because this study examines the data sources that comprise literature related to the title. This research used analytical, comparative and critical descriptive approach to qualitative data. The results of the analysis of pluralism values contained in teaching materials of Islamic Culture History in Class XII is there are some material that is in accordance with pluralism where in the material is very tolerant to multiculturalism that is accompanied by religious pluralism, so that it become the achievement of harmony and mutual respect and those that do not describe the existence of religious pluralism, because the material is widely known to the parties who want to damage good relations between religions and also fight over power by using the name of religion, and it does not accompanied by tolerance so that enmity between religions happened. This shows that there are pluralism values in the History of Islamic Culture of Class XII teaching materials, although on the other hand there are those that do not show Pluralism values. Keywords: Pluralism, Value and History of Islamic Culture.